Physiological response analysis for the diagnosis of drought and waterlogging damage in Prunus yedoensis - Lee, Kyeong-Cheol; Kweon, Hyeongkeun; Sung, Jung-Won; Kim, Yong Suk; Song, Yeong Geun; Cha, Sangsub; Koo, Namin (Forest Science and Technology, 2022)
Drought damage and waterlogging damage are the most frequent abiotic injuries throughout the lifespan of trees. Nonetheless, because the signs of visible damage are similar between these types of injury, physiological indicators must be analyzed to make a scientific differential diagnosis. This study was aimed at investigating growth and physiological indicators of drought (DS) and waterlogging stress (WL) in Prunus yedoensis. Overall growth indices such as tree height, diameter at root collar (DRC), and total dry weight could be ranked in the decreasing order "control > DS > WL." In particular, there was a prominent decrease in root growth in WL, and DRC in DS was lower by 9.2% than DRC before the experiment. As for water saturation deficit (WSD) increased to 37.4% by 28 days after treatment initiation (DAT) in DS. WL showed a sharp decline of photosynthetic indicators such as the net photosynthesis rate (A), stomatal conductance (g s ), and maximum carboxylation rate (V cmax ) starting from 7 DAT. By contrast, DS manifested a significant decrease starting from 14 DAT. The DS had higher levels of leaf and root inorganic components than WL did, suggesting an improvement in the osmoregulatory ability. The overall nutritional status of WL was low due to deterioration of the absorption function of the roots. In both DS and WL, energy transfer rates of photochemical reactions, e.g. absorbed photon leads to reduction further than Q A - (Φ PO ), absorbed photon leads to electron transport further than Q A - (Φ EO ), and absorbed photon leads to reduction of Q A - (Ψ O ), decreased, as did vitality indices, e.g. the performance index on absorption basis (PI abs ), driving force on absorption basis (DF abs ), and the structure function index on absorption basis (SFI abs ). However, WL featured a decrease in Electron transport flux from Q A to Q B (ETo/RC) and Electron transport flux until PSI acceptors (REo/RC), whereas DS experienced a slight increase or almost no change. Consequently, PI abs , DF abs , SFI abs , and the drought factor index are highly sensitive environmental-stress indicators, whereas WSD, DRC growth, chlorophyll a content, ETo/RC, and REo/RC appear to have high potential as diagnostic indicators of drought or waterlogging damage.